Estudo comparativo do custo da semeadura direta na cultura do milho utilizando duas metodologias - Jasper, Samir Paulo [UNESP]; Silva, Paulo Roberto Arbex [UNESP]; Benez, Sérgio Hugo [UNESP] (EIA Energy in Agriculture, 2013)
The present work is about a comparative study of two methodologies (MIALHE and ASABE), used to calculate the cost per hectare in the tillage operation in the culture of corn. The methodology of ASABE presents a higher cost per hectare in relation to the MIALHE proposal, being that the methodologies presents similar costs related to the depreciation expenses, accommodation and insurance. The differences were that in the ASABE proposal, the biggest expenses involved the payment of interest, fuel, lube and handwork, while in the MIALHE methodology, only the expense regarding to maintenance was more. The methodology of ASABE most suitable for management costs per hectare.

O presente trabalho trata do estudo comparativo de duas metodologias (MIALHE e ASABE) utilizadas para o cálculo do custo por hectare na operação de semeadura direta na cultura do milho. A metodologia da ASABE, apresentou um custo por hectare superior em relação a proposta de MIALHE, sendo que as metodologias apresentaram custos semelhantes referentes às despesas com depreciação, alojamento e seguro. As diferenças foram que na proposta da ASABE, as maiores despesas incidiram no pagamento de juros, combustível, lubrificante e mão-obra, enquanto na metodologia de MIALHE, apenas a despesa referente a manutenção foi superior. Sendo a metodologia da ASABE mais indicada para gestão dos custos por hectare.
Comparative study of cost on the no-tillage in the corn culture using two methodologies
Keywords: Agricultural mechanization; Rural management; Information system; Mecanização agrícola; Administração rural; Sistema de informação